Oral rehabilitation of the lower arch using lithium disilicate and dental implants. - Figueira dos Santos, Geraldo; Largo, Muricio Antonio (Brazilian Journal of Implantology and Health Sciences, 2020)
Introduction: The constant search for a harmonic and aesthetic smile raises the level of demand and expectation of patients. The laminated veneers stand out as a treatment option for aesthetic rehabilitation in clinical practice as they provide more conservative procedures and mimic dental structures. The development of new ceramic systems reinforced by lithium disilicate and self-adhesive resin cements favored the increase in longevity and the clinical performance of indirect aesthetic restorations. Case Report: Patient J.B.S, 57 years old, male, complained of edentulous spaces and unpleasant aesthetics in the lower jaw arch. During the anamnesis, deficiency in composite resin restorations in terms of texture and color, and occlusal trauma in the dental element 33 were evaluated. To plan the case, the patient was subjected to a molding with addition silicone, where the material was directed to laboratory for study, being able to define that the entire infrastructure of the implants would be in zirconia. Treatment was performed with 8 crowns on teeth by a system of lithium disilicate, IPSemax on elements 34 to 43 and 45, through wear of the dental elements followed by the insertion of the crowns, and 4 crowns on implantation on elements 35,36,44 and 46 using a zirconia-based system. Implant surgery was performed on these dental elements, with immediate placement of the crowns in lithium disilicate. Final Considerations: The use of lithium disilicate ceramics enabled the functional and aesthetic recovery of the smile when conventional laminated veneer preparations were used, as well as the detailed study based on the addition of silicone molding guided the study towards the correct installation. ceramic implants and crowns.